2015
DOI: 10.1093/ndt/gfv399
|View full text |Cite
|
Sign up to set email alerts
|

PLA2R antibodies, glomerular PLA2R deposits and variations inPLA2R1andHLA-DQA1genes in primary membranous nephropathy in South Asians

Abstract: To conclude, anti-PLA2R and enhanced glomerular PLA2R staining are found in more than two-thirds of Indian PMN cases. A reduction in the anti-PLA2R titer correlated with response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 19 publications
8
113
1
9
Order By: Relevance
“…In another study of 114 newly diagnosed pMN patients from India, Ramachandran et al found, 66.7% anti-PLA 2 R positivity (by ELISA) (24). Lower prevalence in our study may be explained by the fact that we included patients with relapse and refractory disease in our study group.…”
Section: Discussioncontrasting
confidence: 54%
“…In another study of 114 newly diagnosed pMN patients from India, Ramachandran et al found, 66.7% anti-PLA 2 R positivity (by ELISA) (24). Lower prevalence in our study may be explained by the fact that we included patients with relapse and refractory disease in our study group.…”
Section: Discussioncontrasting
confidence: 54%
“…They corroborated a highly significant association between pMN and the risk alleles of HLA-DQA1 and PLA2R1 [59-61]. Furthermore, in a Chinese cohort, Lv et al [60] noted gene-gene interactions between the 2 risk alleles and discovered an association between carrying risk alleles and the presence of anti-PLA2R antibodies in serum as well as the expression of PLA2R in glomeruli.…”
Section: Genetic Studies Of Pmnmentioning
confidence: 74%
“…Recent studies following this paper selected several SNPs as representative from PLA2R1 and the HLA regions791011. The diversity of HLA genes is well-known in human genetics and tightly bound to disease appearance and severity.…”
Section: Discussionmentioning
confidence: 99%